Conservation Based E-Module Innovation to Improve Environmental Literacy in Biodiversity Learning - Eva Mardiana; Irvan Permana; Anna Permanasari; Dadang Jaenudin; Toru Matsumoto; Indriyani Rahman (Jurnal Pendidikan Sains Indonesia, 2026)
Environmental literacy abilities must be developed early on due to the complexity of environmental issues. Based on the literature, young Indonesians typically have a lack of environmental literacy. Environmental literacy must therefore be ingrained from a young age, especially through education. The aims of this study is examining how well a biodiversity e-module centered on conservation may raise junior high school students' environmental literacy. One group pre-test and post-test were employed in the study. Students in the seventh grade at SMPN 1 Wanasalam in the Lebak Regency, Province of Banten were part of the research sample. The environmental literacy tool was updated to align with the biodiversity and conservation content and was adapted from NELA's MSELI. The information gathered was transformed utilizing the NELA methodologies and interpretations to ascertain the degree of environmental literacy among the pupils. N-Gain tests, paired sample t-tests, Wilcoxon tests, and normality tests were among the statistical tests used to assess the effectiveness of the created e-module. The findings demonstrated that pupils' environmental literacy has improved from low to intermediate. In contrast, the average score increased but was constant in the skill, attitude, and conduct areas. According to the N-gain value, which was 0.46 for the knowledge domain, 0.40 for the skills domain, 0.35 for behavior, and 0.23 for the attitude domain, the use of e-modules was quite successful in raising students' environmental literacy